Incubation Period for Neuroinvasive Toscana Virus Infections - Lison Laroche (Centers for Disease Control and Prevention, 2021)
Toscana virus (TOSV) is an emerging pathogen in the Mediterranean area and is neuroinvasive in its most severe form. Basic knowledge on TOSV biology is limited. We conducted a systematic review on travel-related infections to estimate the TOSV incubation period. We estimated the incubation period at 12.1 days.